Разработка и моделирование компьютерных игр с помощью сетей Петри - Шемрикович, А. Д. (ХНУРЕ, 2021)
In modern times, computer games are large systems that have been developed over the years. Large development teams work on the games. It can take years to properly model and balance a game. A modern computer game consists of game processes. The process has different states at certain points in time. The totality of such processes is a state machine. The state of the game objects characterizes a specifically tuned cycle of player interactions through the mechanics available to him with game objects in a certain period of time. In the article one of the methods for modeling a state machine using a Petri net was discusses.
Научный руководитель – ст. преподаватель Новиков Ю.С.
Keywords: разработка компьютерных игр; сети Петри